Harmonization of Local Government Management Study of Regional Head and Deputy Regional Head Couples in North Halmahera Regency - Syarifuddin Usman (Lembaga Penellitian, Pengabdian dan Publikasi (LP3M), UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2025)
The breakdown of cooperation between regional leaders is one of the problems in the direct election system in the era of regional autonomy. This is not only evident at the provincial level, involving governors and their deputies, but also at the regency and city levels, involving regents and their deputies, as well as mayors and their deputies. The most reasonable explanation for this breakdown of cooperation is the struggle for influence between regional leaders and their deputies. Both claim to have contributed to winning the election. Another factor that influenced Djohermansyah Johan's report in mediaindonesia.com was that of the 244 regional elections held in 2010, 862 or 94% of regional head and deputy regional head pairs elected in the regional elections broke up. Only 6.15% or 52 pairs of regional heads and deputy regional heads remained harmonious and returned for a second term. This indicates that the results of the regional elections have not produced solid and qualified leaders. Pairs running in the second term of the Pilkada include those in North Maluku. There are three pairs of regional heads and deputy regional heads, including the Regent and Deputy Regent of North Halmahera. The results of the study show that the regional heads and deputies in North Halmahera Regency were able to maintain harmonious governance until the second term because they were able to maintain the boundaries of their authority and the social capital possessed by each candidate pair.